Predicting the optimal timing for system upgrades in binary geothermal power Plants: A thermodynamic and exergetic approach - Gurturk, Mert (Pergamon-Elsevier Science Ltd, 2025)
This study seeks to identify the optimal timeframe for implementing system upgrades or integrating alternative technologies into a binary geothermal power plant in response to the gradual cooling of the geothermal resource. Determining this timeframe is especially critical from an investor's standpoint, as it significantly influences the financial planning required for additional drilling operations or the adoption of supplementary systems. The primary focus of this study is to determine the critical point in time at which the system can no longer operate at full capacity. Unlike many existing studies, the proposed thermodynamic model incorporates both the geothermal fluid temperature and the ambient environmental temperature into its calculations. The model has been validated through comparisons with previously published research, and the results have been analyzed within the framework of theoretical constraints. To define the theoretical constraints, the power plant's operational timeline was evaluated hourly over a 25-year period, taking into account Carnot efficiency, phase equilibrium using P-h and T-s diagrams, and the calculated energy, exergy, and thermal efficiency parameters. The system's total installed capacity is 24 MW; however, the analysis indicates that after ten years of operation, the plant can no longer maintain full capacity, resulting in approximately 51,645 h of operation below the nominal output. Furthermore, specific time intervals were identified during which elevated ambient temperatures led to a reduction in power generation to as low as 7.6 MWh.
Keywords: Exergy; Geothermal; Technical feasibility; Resource cooling effects